Neznámý městský řád pro Náchod ze šedesátých let 16. století - Ludmila Sulitková (Theatrum Historiae)
The author has recently found in the resources of Archiv Národního muzea (National Museum Archives) unknown municipal order for the Eastbohemian town of Náchod that was given by the owner of the Náchod estate Albrecht Smiřický of Smiřice in the mid-1560s. In this article, the author tries to find a possible model for the above mentioned order and comes to conclusion that it is very similar to the older order published by Vilém /Wilhelm/ of Pernstein for Pardubice in 1512. This order might remain in the Náchod municipal or patrimonial archives from the times of the Pernstein rule (Vojtěch /Adalbert/ of Pernstein held Náchod in 1533–1534, his brother Jan /Johann/ of Pernstein followed him in 1534–1544). Based on the analysis of both the orders and on comparison with other known municipial orders the author brings hypothesis that the Pernsteins paid the biggest attention to the regimentation of municipal conditions in their towns.